2017
DOI: 10.1038/s41598-017-06504-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Porosity on Fatigue Crack Initiation in Additively Manufactured Titanium Components

Abstract: Without post-manufacture HIPing the fatigue life of electron beam melting (EBM) additively manufactured parts is currently dominated by the presence of porosity, exhibiting large amounts of scatter. Here we have shown that the size and location of these defects is crucial in determining the fatigue life of EBM Ti-6Al-4V samples. X-ray computed tomography has been used to characterise all the pores in fatigue samples prior to testing and to follow the initiation and growth of fatigue cracks. This shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
187
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(201 citation statements)
references
References 37 publications
14
187
0
Order By: Relevance
“…Both elastic and elasto‐plastic FEM simulations show that near surface pores (0.6 < s / r < 1.2) are more harmful to the fatigue cracking resistance of hybrid laser welded AA7020‐T651 joints in terms of notable stress concentration. Similar conclusions have also been derived for different materials with various defects …”
Section: Experiments and Simulationssupporting
confidence: 87%
See 3 more Smart Citations
“…Both elastic and elasto‐plastic FEM simulations show that near surface pores (0.6 < s / r < 1.2) are more harmful to the fatigue cracking resistance of hybrid laser welded AA7020‐T651 joints in terms of notable stress concentration. Similar conclusions have also been derived for different materials with various defects …”
Section: Experiments and Simulationssupporting
confidence: 87%
“…Compared with surface pores, the subsurface pores appear to be less harmful to the fatigue regardless of the size. The similar conclusion was confirmed on AM Ti alloys even though relatively less data are available . More experiments and theoretical aspects are required to show the point.…”
Section: Experiments and Simulationssupporting
confidence: 62%
See 2 more Smart Citations
“…The results obtained by nondestructive CT analysis can be used to identify critical pores with a high volume and characterize their size, shape, and position in the specimen before fatigue testing. For a titanium alloy processed by electron beam melting technique, it could be shown that not only the size but also the proximity to the surface and the pore aspect ratio, which was detected by CT measurements, have a high influence on the fatigue behavior …”
Section: Introductionmentioning
confidence: 99%